2017
DOI: 10.1177/0269215517719485
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre study of how goal-setting is practised during inpatient stroke rehabilitation

Abstract: Objective: To describe goal-setting during in-patient stroke rehabilitation.Design: There were two stages: An electronic questionnaire for multi-disciplinary teams and an analysis of goal-setting documentation for rehabilitation patients. Setting: Five in-patient stroke unitsParticipants: Staff involved in goal-setting and patients undergoing stroke rehabilitation in Results: 13 therapists and 49 patients were recruited. 351 documented goals were examined. All units used therapist-led goal-setting (60% of goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 23 publications
2
27
1
10
Order By: Relevance
“…5 To improve patient-centered goal-setting within geriatric rehabilitation, knowing what rehabilitation goals comprise from a patient perspective and how goals may change over time is important. Although some studies have investigated goal-setting together with the patient, they were mainly conducted within brain 68 or stroke rehabilitation 914 and provide insight into the goal-setting process rather than patient goals. One of the few studies that looked into geriatric rehabilitation goals from a patient perspective considered short-term goals within 24 hours after admission and found that patients’ most common goals were “going home” and “regaining independence in self-care.” Whether and how these goals change once they are attained and patients are discharged, however, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…5 To improve patient-centered goal-setting within geriatric rehabilitation, knowing what rehabilitation goals comprise from a patient perspective and how goals may change over time is important. Although some studies have investigated goal-setting together with the patient, they were mainly conducted within brain 68 or stroke rehabilitation 914 and provide insight into the goal-setting process rather than patient goals. One of the few studies that looked into geriatric rehabilitation goals from a patient perspective considered short-term goals within 24 hours after admission and found that patients’ most common goals were “going home” and “regaining independence in self-care.” Whether and how these goals change once they are attained and patients are discharged, however, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Even though goal setting during stroke rehabilitation has been generally referred to as a single activity that is isolated from other rehabilitation processes in most literature [9][10][11], the experts felt it should be an integral part of the stroke survivors' assessment and treatment management plans. This position is similar to the report of Plant and Tyson [12] With regards to the implementation strategies, the multi-disciplinary team-based approach (MDT) was excluded, as experts felt that the interdisciplinary approach (IDT) was more suited for delivering the RTW intervention. Although MDT has been associated with improvements in the quality of stroke care by policy makers and clinical guideline developers in the literature [16][17][18][19], considering the context in which the RTW would take place and the stage during the care continuum when RTW intervention is to be implemented, the experts felt that the conceivable value of integrated team action may not be achieved using MDT.…”
Section: Discussionmentioning
confidence: 70%
“…• When client is independent in performing leisure activities • When client is fully reintegrated in the community (such as participation in social groups) setting during stroke rehabilitation has been generally referred to as a single activity that is isolated from other rehabilitation processes [19,23,24]. Plant and Tyson [25], on the contrary asserted that goal setting process as well as patient's assessment during stroke rehabilitation are clearly interlinked. The above authors suggested the integration of the two processes in long term post stroke rehabilitation.…”
Section: Period For the Rtw Interventionmentioning
confidence: 99%